High-Order Iterative Methods for the DMP Inverse - Xiaoji Liu; Naping Cai (Journal of Mathematics)
We investigate two iterative methods for computing the DMP inverse. The necessary and sufficient conditions for convergence of our schemes are considered and the error estimate is also derived. Numerical examples are given to test the accuracy and effectiveness of our methods.